The Dutch national guideline on metastases and hematological malignancies localized within the spine; a multidisciplinary collaboration towards timely and proactive management. (September 2018) - Groenen, Karlijn H.J.; van der Linden, Yvette M.; Brouwer, Thea; Dijkstra, Sander P.D.; de Graeff, Alexander; Algra, Paul R.; Kuijlen, Jos M.A.; Minnema, Monique C.; Nijboer, Claudia; Poelma, Davey L.H.; Rolf, Christa; Sluis, Tebbe; et al.
Abstract: Here, we describe the development of a Dutch national guideline on metastases and hematological malignancies localized within the spine. The aim was to create a comprehensive guideline focusing on proactive management of these diseases, enabling healthcare professionals to weigh patient perspectives, life expectancy, and expected outcomes to make informed treatment recommendations. A national multidisciplinary panel consisting of clinicians, a nurse, a patient advocate, an epidemiologist, and a methodologist drafted the guideline. The important role of patients in the realization of the guideline enabled us to identify and address perceived shortcomings in patient care. The guideline covers not only metastatic epidural spinal cord compression, but also the treatment of uncomplicated metastases and hematological malignancies localized within the spine. The guideline is applicable in daily practice and provides an up-to-date and concise overview of the diagnostic and treatment possibilities for patients suffering from a disease that can have a serious impact on their quality of life. Suggestions for the practical implementation of patient care in hospitals are also provided, including approaches for pursuing proactive management. The crucial role of the patient in decision making is emphasized in this guideline.